STRATEGY TO REACTIVATE THE EXISTING ATAPUPU FISH AUCTION FACILITY FOR FOOD SECURITY IN THE BELU DISTRICT - Dwi Putra, Rivaldi Ananda; Saputri, Rizki Ananda; Lopes, Martina Mendonca; Surianingsih, Ketut Epi (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2022)
Atapupu Fish Auction Facility (Tempat Pelengan Ikan or TPI) is a place used for fish landing, whether there is a building for mooring (pier) in that place, a sale of fish/sea products, whether by auction or not. TPI Atapupu has an impact on supervision and facilities for fishery resources so that they can be useful as food ingredients in Belu Regency. Currently, the TPI Atapupu has not been operating due to various obstacles since 2007. Therefore, this study aims to determine the reactivation strategy of TPI Atapupu for food security in the Belu Regency. The qualitative approach in this study explains the appropriate ends, means, and ways strategies in the reactivation of TPI Atapupu. Strategy development is based on an analysis of the relationship between TPI Atapupu and food security and the operational constraints of TPI Atatpupu. Food security is the fulfillment of food needs for households which is reflected in the availability of sufficient food, both in quantity and quality, evenly distributed, and affordable. The role of TPI in food security is to be able to provide a sufficient quantity of food; maintain food quality starting from quality, safety, and guaranteed nutrition; and the fulfillment of food needs for the people of Belu Regency. The implementation of the TPI Atapupu reactivation strategy for Food security in the Belu Regency is beneficial for policymakers so that later it can become a guideline in policy making.Â 